Implementasi Model Inkuiri Terbimbing Berbasis Lesson Study untuk Melatihkan Kemampuan Mengolah Informasi Siswa SMP pada Materi Getaran Dan Gelombang: Penelitian - Shintia Ani Fatimatus Zahro; Dyne Rizki Puspitasari; Imraatul Mufidah; Siti Zubaidah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This learning aimed to train the information-processing skills of 8th-grade junior high school students on the topic of vibrations and waves through the implementation of the guided inquiry model. The main problem encountered was the low ability of students to process information, indicated by their tendency to focus only on the final results without understanding the process, as well as the emergence of irrelevant questions during the lesson. The activity was carried out in three lesson study stages: Plan, Do, and See. The inquiry model was implemented with the teacher acting as a facilitator guiding the processes of exploration, investigation, and reflection. The results showed an improvement in students' information-processing abilities, with achievements in the aspects of analysis (77%), inference (70%), and evaluation (81%). This learning has proven to be effective in training critical thinking skills through a guided inquiry approach. In conclusion, the implementation of inquiry-based learning within the framework of lesson study can be a meaningful strategy to improve students' ability to process information. For future implementation, it is recommended that time management in learning be more emphasized, the model teacher provide more active assistance especially during experimental activities, and further testing of the question instruments on wave material be conducted to obtain stronger and more comprehensive data.